Crescimento econômico e desacoplamento do uso de recursos naturais e de impactos ambientais: evidências para o Brasil - Soares, Layza da Rocha [UNESP] (2015)
The present dissertation aims to investigate the long-term relationship between economic growth and the environment in Brazil through the construction of resource and impact decoupling indicators. The study is embedded on empirical studies which address that relationship as well as on the discussion about decoupling - the key concept of the Green Economy Initiative, which can be found within the realm of the theoretical literature on sustainable development from the two schools of thought - Environmental Economics and Ecological Economics. To this end, indicators of resource use by the Material Flow Accounting method (MFA) are measured consisting of all categories of materials (biomass, fossil fuels carriers, non-metallic minerals and metallic minerals) for the period between 1970 and 2013. In addition, indicators of impacts related to different environmental aspects (air, land, water, biodiversity, sanitation) are used in the course of our analysis. The results show a high growth in per capita consumption of natural resources and exports of materials in the 44 years of study, where the resources extracted are mainly biomass while non-metallic minerals are secondary. Brazil has a deficit Physical Trade Balance owing especially to the exports of biomass (soybean, sugarcane) and metal ores (iron), and is still found to be dependent on the imports of fossil fuels and chemical minerals (fertilizer). Improvements in environmental indicators are also verified, particularly a reduction of GHG emissions between 1990 and 2012, as a result of the decrease in deforestation rates in the Legal Amazon. This empirical evidence, in effect, is in line with the occurrence of absolute decoupling of environmental impacts - with the exception of those that relate to earth dimension - and the coupling of natural resources in Brazil. This result is a clear indication that although the country is moving toward a more sustainable growth pattern, it is, however...